THE RELATIONSHIP BETWEEN BODY SHAMING WITH SELF-ESTEEM AND SUICIDE RISK AMONG LATE ADOLESCENTS AT JAKARTA, INDONESIA: A CROSS-SECTIONAL STUDY - Rafifah, Zalfa Kamila; Sianturi, Renta (Journal of Community Mental Health and Public Policy, 2025)
Background: Physical changes during teenagers such as weight gain, height increase, and body shape transformation, can negatively affect self-perception. These changes often lead to body shaming behavior, which contributes to low self-esteem and increased suicide risk. Purpose: To determine the relationship between body shaming, self-esteem, and suicide risk. Methods: A cross-sectional study was conducted in January 2024 involving 66 students from Vocational High School X in Jakarta. Data were collected using three instruments: the Body Shaming Questionnaire, the Coopersmith Self-Esteem Inventory (Adult Form), and the Suicidal Behaviors Questionnaire-Revised (SBQ-R). Validity testing on 103 students from another school yielded 18 valid items for Body Shaming, 23 for CSEI, and 4 for SBQ-R. Results: There was a significant relationship between body shaming and self-esteem (p = 0.007; OR = 4.033; 95% CI: 1.445–11.257), and between body shaming and suicide risk (p = 0.040; OR = 2.875; 95% CI: 1.033–8.000). Conclusion: Body shaming is associated with lower self-esteem and increased suicide risk among late teenagers in Vocational High School, Jakarta. Abstrak Latar Belakang: Perubahan fisik pada masa remaja seperti peningkatan berat dan tinggi badan serta perubahan bentuk tubuh dapat menimbulkan persepsi negatif terhadap diri sendiri. Hal ini sering memicu perilaku body shaming yang berdampak pada penurunan harga diri dan peningkatan risiko bunuh diri. Tujuan: Mengetahui hubungan antara body shaming dengan harga diri dan risiko bunuh diri. Metode: Penelitian cross-sectional ini melibatkan 66 siswa di SMK Perbankan Nasional Jakarta pada Januari 2024. Data dikumpulkan menggunakan tiga instrumen: Kuesioner Body Shaming, Coopersmith Self Esteem Inventory (CSEI) versi dewasa, dan Suicidal Behaviors Questionnaire-Revised (SBQ-R). Uji validitas dilakukan pada 103 siswa sekolah lain menghasilkan 18 item valid untuk Body Shaming, 23 item valid untuk CSEI, dan 4 item valid untuk SBQ-R. Hasil: Terdapat hubungan signifikan antara body shaming dan harga diri (p = 0,00; OR = 4,03; CI 95%: 1,445–11,257) serta hubungan antara body shaming dan risiko bunuh diri (p = 0,04; OR = 2,87; CI 95%: 1,033–8,000). Kesimpulan: Body shaming berhubungan dengan harga diri rendah dan peningkatan risiko bunuh diri pada remaja akhir di SMK Perbankan Nasional Jakarta.